INTERFACE - Grudin, Jonathan (DAIMI Report Series, 1990)
This is an essay on the ways in which we have used, now use, and might use the terms ''user,'' ''interface,'' and ''designer,'' and their various combinations. Current usage conceals important changes in our field -- in some cases, the words have outlived their original usefulness in the engineering environment, however comfortable we now feel with them. They may conceal aspects of the environments in which computers are used today -- work environments often very unlike the engineering environment, which are increasingly important for systems developers to understand. The power of words is not total, but they may subtly and indirectly inhibit the adoption of new areas of research and approaches to development. Computer systems are presented as highly complex artifacts, the products of a continuous design process that has engaged countless individuals, incorporating considerable implicit understanding of people and their work. The terminology brought forward from the field's origins can obscure this history and the need to maintain and even strengthen the focus on human psychology and work.